2020
DOI: 10.36333/k2a02
|View full text |Cite
|
Sign up to set email alerts
|

Investing in Nature as the true engine of our economy: A 10-point Action Plan for a Circular Bioeconomy of Wellbeing

Abstract: IntroductionTransformative action points to move towards a Circular Bioeconomy of Wellbeing Focus on sustainable wellbeing Box I Gross Domestic Product versus Genuine Progress Indicator Invest in nature and biodiversityBox II Renewable natural capital and nature-based solutions are key for a circular bioeconomy Box III Connecting private forest owners for collective biodiversity protection in Denmark Generate an equitable distribution of prosperity Box IV Payments for watershed protection in Ecuador Box V Biop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…Nature-based solutions provide a strategy for protecting ecosystems while simultaneously overcoming societal challenges and positively impacting wellbeing and biodiversity. The SDGs encourage and complement the implementation of nature-based solutions [43].…”
Section: The Circular Economy and Nature Based Solutionsmentioning
confidence: 99%
“…Nature-based solutions provide a strategy for protecting ecosystems while simultaneously overcoming societal challenges and positively impacting wellbeing and biodiversity. The SDGs encourage and complement the implementation of nature-based solutions [43].…”
Section: The Circular Economy and Nature Based Solutionsmentioning
confidence: 99%
“…Ecosystem resilience can be defined as the capacity over time for an ecosystem to resist external stress and disturbances or restore ecosystem structures and functioning to a predisturbance stable state [79]. Ecosystem resilience can have an antagonistic relationship with economic resilience, as the latter benefits from forestry-related forest disturbance (e.g., harvesting) as a source of income.…”
Section: Discussionmentioning
confidence: 99%
“…An explorative qualitative study based on the perspectives of sustainability researchers suggested that there is a potential to couple circular (e.g., efficiency, recycling, reusing and upcycling) and green economy solutions (e.g., engaging business, customers and investors in the conservation of biodiversity and ecosystems) [19]. Palahí et al [51] recently proposed a series of action points based on a biodiversity-based circular bioeconomy, in order to rethink industrial, urban, food and health systems and promote participation and a more equitable distribution of prosperity. Furthermore, the term 'nature-positive economy' has very recently emerged in the context of sustainable business and finance [49,82].…”
Section: Sufficiencymentioning
confidence: 99%